Innovating with nature: from nature-based solutions to nature-based enterprises - Collier, Marcus; Rhodes, Mary-Lee (My University, 2021)
Nature-based solutions (NBS) to address societal challenges have been widely recognised and adopted by governments in climate change and biodiversity strategies. Nevertheless, significant barriers exist for the necessary large-scale implementation of NBS and market development is still in its infancy. This study presents findings from a systematic review of literature and a survey on private sector agents in the planning and implementation of NBS, with the aim to identify them. In this study, we propose a typology for organisations delivering NBS and a categorisation of their economic activities. The most common organisation type found is nature-based enterprise which offers products or services where nature is a core element and used sustainably and engages in economic activity. Moreover, eleven categories of economic activities were identified, ranging from ecosystem restoration, living green roofs, and eco-tourism to smart technologies and community engagement for NBS. Nature-based enterprises contribute to a diverse range of sustainable economic activities, that standard industry classification systems do not adequately account for. The recognition of the value created by these activities is essential for designing effective policy support measures, and for market development of the sector and its potential to facilitate the wider adoption of NBS.
PUBLISHED
Nature-based solutions (NBS) to address societal challenges have been widely recognised and adopted by governments in climate change and biodiversity strategies. Nevertheless, significant barriers exist for the necessary large-scale implementation of NBS and market development is still in its infancy. This study presents findings from a systematic review of literature and a survey on private sector agents in the planning and implementation of NBS, with the aim to identify them. In this study, we propose a typology for organisations delivering NBS and a categorisation of their economic activities. The most common organisation type found is nature-based enterprise which offers products or services where nature is a core element and used sustainably and engages in economic activity. Moreover, eleven categories of economic activities were identified, ranging from ecosystem restoration, living green roofs, and eco-tourism to smart technologies and community engagement for NBS. Nature-based enterprises contribute to a diverse range of sustainable economic activities, that standard industry classification systems do not adequately account for. The recognition of the value created by these activities is essential for designing effective policy support measures, and for market development of the sector and its potential to facilitate the wider adoption of NBS.
Keywords: Nature-based enterprise; Nature-based solutions; Sustainable development; Classification of economic activities; Smart & Sustainable Planet; INNOVATION; NATURE-BASED SOLUTIONS; Nature-based enterprise; SUSTAINABLE DEVELOPMENT; Social Innovation